The Alternative Business Psychology Application in Green Industry Program Towards the Competitiveness of Asean Economic Community 2016 - Murty Magda Pane (Bina Nusantara University, 2016)
Penetrating the era of the ASEAN Economic Community, the requisite of national business environment to prevail the competitionwas more exorbitant and formidable. A corporation could implement a program of Green Industry from the government to improve the effectiveness and efficiency.In enhancing the efficiency of Green Industry implementation, a corporate attempted to apply the theories in business psychology as an alternative of intervention.The objective of this study was to give the alternative intervention to the manufacturing business in implementing the Green Industry program. This study used the literature study as a method and limited the scope to develop the organization using the theory of business psychology as the intervention. The change management as part of the business psychology is the result of study after comparing the theories in the literature study method.